Perseptron berbilang lapisan algoritma perambatan ke belakang:Konsep rangkaian neural tiruan - Aini Hussain,; Zainul Abidin M. Sharrif,; Masuri Othman, (1993)
The main objective of this paper is to serve as an introduction to the process of designing and training of a neural network. A simple implementation of a nonlinear separable function (e.g. exclusive OR function) using the backpropagation training algorithm and feedforward multilayer perceptron is used as an example. Finally, the paper summarizes the advantages and disadvantages of the Neural Networks. In addition, it also discusses the implementation of the neural network appraoch to voice/unvoice problems